Preparation and Characterization of Y2O3, Sio2 Doped By Eu2O3 as Luminescent Ink - Merzah, Amel Salih; Ibrahim, Abdulrahman Saleh (Iraqi Journal of Chemical and Petroleum Engineering, 2015)
This article includes the preparation of luminescence materials from rare earth (Eu ) ion doping Yttrium Oxide (Y2O3) 70% and SiO2 25% and study the characteristics of phosphors for ultraviolet to visible conversion. The phosphor materials have been synthesized by two steps: Preparing the powder by solid state method using Y2O3, SiO2 and Eu2O3 with doping materials concentration (70%, 25% and 5%) respectively and different calcination temperature (1000, 1200 and 1400 oC). The second step is to prepare the colloid solution by dispersing the produced powder in a polyvinyl alcohol solution (4%) . Powder preparation is achieved by mixing the powder according to weight percentage, milling by a ball mill using yttrium stabilized zirconia with the aid of propanol for homogenization then calcination the mixture at the above temperatures. The produced powder was characterized by X-Ray diffraction. Colloid preparation is achieved by dissolving the PVA in water (4%) then dispersing the powder into the solution by using the hot plate magnetic stirrer and ultrasonic bath. The produced powder was characterized by using Fourier transform infrared (FTIR) and Photoluminescence spectra (PL). The results of photoluminescence spectra show that samples were emitting red color with wave length of 612nm. The intensity of emission was increased with increasing calcination temperature.